Circumflex Model of Family Therapy: Initiating Its Application on Parenting Mistakes to Child Early Age (KONSELING RELIGI, 2019)
The golden age in the development of early childhood requires more attention amid the emergence of the phenomenon of shifting family functions in the millennial era. Father's function and mothers who experience shifts are thought to have the potential for emergence of parenting problems.  The golden age is in need of good parenting, because an error of parenting during this period a significant impact on adulthood. This requires family therapy that is good and feasible to be used in intervening in cases of parenting errors with early childhood. This article aims to describe the theory of family therapy in the circumflex model popularized by Olson, analyzing and initiating its application in cases of parenting errors in early childhood. The idea of applying the therapy is complemented by the design of the stages and forms of therapy. The results of the study show that theoretically it is possible to apply circumcision family model therapy in cases of early childhood parenting errors, because early childhood leads to an internal problem three important dimensions in the circuit model to create a healthy and balanced family, namely the dimensions of closeness, adaptability or flexibility and family communication. The therapeutic design for families who experience parenting errors in early childhood is arranged in stages, stages or sessions of one to ten.